2017
DOI: 10.1093/ejcts/ezx218
|View full text |Cite
|
Sign up to set email alerts
|

Single-centre experience with the frozen elephant trunk technique in 251 patients over 15 years†

Abstract: FET results are comparable with those of the published results of the conventional elephant trunk technique. FET is an ideal landing zone for subsequent transfemoral endovascular completion. Patients with graft infections may have dismal results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 17 publications
8
102
0
3
Order By: Relevance
“…A recent study has found that at the time of initial repair for TAAD in MFS, a more aggressive surgical approach seems to be superior to limited repair (29). However, there is scarce data on the long-term outcomes of such extensive repair for TAAD in such patients (19,22,30). The current cohort expanded the special subset of MFS patients in our experience (17,22,31), who, following a prior Bentall procedure, developed TAAD involving the arch, which was repaired in a reoperative setting with the extensive FET technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has found that at the time of initial repair for TAAD in MFS, a more aggressive surgical approach seems to be superior to limited repair (29). However, there is scarce data on the long-term outcomes of such extensive repair for TAAD in such patients (19,22,30). The current cohort expanded the special subset of MFS patients in our experience (17,22,31), who, following a prior Bentall procedure, developed TAAD involving the arch, which was repaired in a reoperative setting with the extensive FET technique.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reoperation for arch dissection was required in 40.9-49% of patients (15,16). As a result, the more extensive total arch replacement (TAR) (15) or in combination with the frozen elephant trunk (FET) has been advocated as an approach to TAAD involving the aortic arch in patients with MFS during initial surgical treatment (17)(18)(19), despite concerns on the mortality and paraplegia risks and limited imaging follow-up (20,21). Although our previous study has proved the efficacy and durability of TAR + FET for TAAD in MFS (22), data is scarce regarding the longterm outcomes of this technique for TAAD in Marfan patients who have undergone a Bentall operation previously.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results confirmed that the need for reintervention is due to the characteristics of the primary disease, and not because of the failure of FET's prosthesis. Besides, FET simplified reintervention in the distal segments, providing a more appropriate landing zone for endovascular completion …”
Section: Discussionmentioning
confidence: 99%
“…In particular the false lumen in the descending aorta thromboses in a large proportion of patients, reducing the risk for further late distal malperfusion syndromes. Several groups have, indeed, published quite satisfactory results with the use of this method, in particular after surgery for acute or chronic aortic dissection (43)(44)(45)(46).…”
Section: The "Frozen Elephant Trunk" Techniquementioning
confidence: 99%